2007
DOI: 10.1515/jpem.2007.20.4.527
|View full text |Cite
|
Sign up to set email alerts
|

Stressful Life Events and Psychological Dysfunctions Before the Onset of Type 1 Diabetes Mellitus

Abstract: These results support the hypothesis that stressful life events and psychological dysfunctions are associated with DM1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 31 publications
5
22
1
Order By: Relevance
“…Comparison with other studies Our prospective study confirms the findings from several retrospective studies that observed an association between type 1 diabetes and previous experiences of SLEs [7][8][9][10][11][12][13][14][15][16][17]. Some previous studies found an association with stressful life events in general [9,10,[14][15][16], while other studies were more limited to specific events [7,8,13,17], events judged as negative for the child [12] or specific events in a specific age group [11].…”
Section: Strengths and Limitations Of The Studysupporting
confidence: 89%
See 4 more Smart Citations
“…Comparison with other studies Our prospective study confirms the findings from several retrospective studies that observed an association between type 1 diabetes and previous experiences of SLEs [7][8][9][10][11][12][13][14][15][16][17]. Some previous studies found an association with stressful life events in general [9,10,[14][15][16], while other studies were more limited to specific events [7,8,13,17], events judged as negative for the child [12] or specific events in a specific age group [11].…”
Section: Strengths and Limitations Of The Studysupporting
confidence: 89%
“…Some previous studies found an association with stressful life events in general [9,10,[14][15][16], while other studies were more limited to specific events [7,8,13,17], events judged as negative for the child [12] or specific events in a specific age group [11]. However, previous retrospective studies have the methodological shortcoming of recall bias, which has been, for the first time on an individual level, avoided in the current study.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 70%
See 3 more Smart Citations